Euro puppets: The European Commission's remaking of civil society - Christopher Snowdon (Institute of Economic Affairs (IEA), 2013)
European Commission spending millions on pro-EU lobby groupsExecutive summary:With public confidence in the European project waning, the idea of initiating a 'civil dialogue' with the public emerged in the mid-1990s as a way of bolstering the EU's democratic legitimacy.Citizens have not been consulted directly, however. Instead they have been ventriloquised through 'sock puppet' charities, think tanks and other 'civil society' groups which have been hand-picked and financed by the European Commission (EC). These organisations typically lobby for closer European integration, bigger EU budgets and more EU regulation.The composition of 'civil society' at the EU level is largely dictated by which groups the Commission chooses to fund. There has been a bias towards centre-left organisations, with a particular emphasis on those promoting policies that are unpopular with the public, such as increasing foreign aid, restricting lifestyle freedoms and further centralising power within EU institutions.The EC's favoured civil society organisations are also marked by a homogeneous worldview and similarity of jargon. The literature and websites of these groups suffocate the reader with vague rhetoric about 'stakeholders', 'sustainability', 'social justice', 'capacity building', 'fundamental rights', 'diversity', 'equity' and 'active citizenship'.Many of the groups which receive the Commission's patronage would struggle to exist without statutory funding. For example, Women in Europe for a Common Future received an EC grant of exteuro1,219,213 in 2011, with a further exteuro135,247 coming from national governments. This statutory funding made up 93 per cent of its total income while private donations contributed exteuro2,441 (0.2 per cent) and member contributions just exteuro825 (0.06 per cent).There is virtually no funding for organisations which seriously question the Commission's direction of travel. By contrast, groups that favour closer union and greater centralisation are generously funded. The 'Europe for Citizens' programme which 'gives citizens the chance to participate in making Europe more united, to develop a European identity, to foster a sense of ownership of the EU, and to enhance tolerance and mutual understanding' has a exteuro229 million budget for 2014-20.Substantial EU funds are also used to support organisations that share the Commission's environmentalist agenda. The Green 10 represent the largest of Europe's environmental lobby groups, but dozens, if not hundreds, of like-minded ecological organisations also receive EU funding. The Commission freely admits that funds are given to environmental groups 'to support policy development'.Civil society groups in non-member countries are another funding priority for the Commission. In 2012/13, its Neighbourhood Civil Society Facility had a exteuro22 million budget to be distributed to groups in Eastern Europe, North Africa and the Middle East, later increased to exteuro45.3 million. Many Youth in Action grants have been given to projects in potential new member states such as 'Unite Unite Europe!' (Serbia), 'Be Active, Be European!' (Albania) and 'Citizen of my country, citizen of my Europe!!' (Kosovo).The EC's policy of picking allies and supporting them with taxpayers' money has made the system more elitist and less democratic.
Keywords: 330; Society; European integration; Interest policy; EU states; Gesellschaft; Europäische Integration; Interessenpolitik; EU-Staaten